Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

Given the conditional statement [tex]\( \sim p \rightarrow q \)[/tex], which statement is logically equivalent?

A. [tex]\( p \rightarrow \sim q \)[/tex]
B. [tex]\( \sim p \rightarrow \sim q \)[/tex]
C. [tex]\( \sim q \rightarrow \sim p \)[/tex]
D. [tex]\( \sim q \rightarrow p \)[/tex]


Sagot :

To determine which statement is logically equivalent to the given conditional statement [tex]\(\sim p \rightarrow q\)[/tex], we'll use logical equivalences, specifically focusing on the concept of contrapositives.

A conditional statement of the form [tex]\(A \rightarrow B\)[/tex] is logically equivalent to its contrapositive, [tex]\(\sim B \rightarrow \sim A\)[/tex]. This means that the truth value of the conditional statement remains the same when we switch the implication around and negate both parts.

Given the statement [tex]\(\sim p \rightarrow q\)[/tex]:

1. Identify the components of the statement:
- [tex]\(A\)[/tex] in this case is [tex]\(\sim p\)[/tex].
- [tex]\(B\)[/tex] in this case is [tex]\(q\)[/tex].

2. Form the contrapositive of [tex]\(\sim p \rightarrow q\)[/tex]:
- The contrapositive is obtained by negating both parts and reversing the implication.
- So, we negate [tex]\(q\)[/tex], which gives [tex]\(\sim q\)[/tex].
- We negate [tex]\(\sim p\)[/tex], which simplifies to [tex]\(p\)[/tex].
- The contrapositive of [tex]\(\sim p \rightarrow q\)[/tex] is then [tex]\(\sim q \rightarrow p\)[/tex].

3. Verify the options provided to identify the equivalent statement:
- [tex]\(p \rightarrow \sim q\)[/tex]
- [tex]\(\sim p \rightarrow \sim q\)[/tex]
- [tex]\(\sim q \rightarrow \sim p\)[/tex]
- [tex]\(\sim q \rightarrow p\)[/tex]

Among these, the statement that matches the contrapositive we derived, [tex]\(\sim q \rightarrow p\)[/tex], is:

[tex]\(\sim q \rightarrow \sim p\)[/tex]

Therefore, the statement that is logically equivalent to [tex]\(\sim p \rightarrow q\)[/tex] is:

[tex]\(\sim q \rightarrow \sim p\)[/tex]